THE RELATIONSHIP OF INDIVIDUAL‐ AND COMMUNITY‐LEVEL SOCIOCULTURAL AND NEIGHBORHOOD FACTORS TO THE MENTAL HEALTH OF ETHNIC GROUPS IN TWO LARGE U.S. CITIES. Issue 1 (January 2016) - Alamilla, Saul G.; Scott, Marc A.; Hughes, Diane Leslie
Abstract : Using multilevel modeling, the present study examines psychological well‐being as a function of sociocultural factors, neighborhood disadvantage, neighborhood fragmentation, and neighborhood integration, along with individual factors among a sample of 1, 306 African and Latino/a Americans living in New York City and Chicago neighborhoods. Neighborhood blocks were prestratified based on racial/ethnic and economic characteristics and then randomly selected within predefined strata, resulting in a total of 140 block (neighborhood) groups. A means‐as‐outcome and slopes‐as‐outcome model was fit to the data. Intraclass correlation coefficients for psychological well‐being for the fully unconditional model revealed that 15% of the variance in psychological well‐being is between neighborhoods. Results from subsequent model building revealed differences in mean levels of psychological well‐being as well as heterogeneity between neighborhoods through varying predictor effects on psychological well‐being (i.e., certain predictor effects varied across neighborhoods). Sociocultural variables such as cultural identity, religious/spiritual coping, and family obligation were significantly associated with psychological well‐being, generally beneficial, and sometimes varying with generation status and across neighborhoods. Different dimensions of neighborhood disadvantage and fragmentation emerged as important factors, although neighborhood integration did not. Our final models explained a substantial proportion of the variance in psychological well‐being within and between neighborhoods. They also revealed the contextual and conditional nature of sociocultural factors.